Program Retensi Pelanggan dan Kualitas Layanan terhadap Loyalitas Pelanggan dengan Keputusan Pembelian sebagai Variabel Mediasi - Pamikatsih, Nufaisa; Herawati, Aty (IPM2KPE, 2024)
Customer retention determines the continuity of the business relationship between the customer and the company. The retention program at Alfamart is already good with the Ponta card, which functions to collect points every time a customer makes a purchase. This research aims to. The research method used is explanatory research with a quantitative research approach. The results showed that there was a significant influence with a positive direction between customer retention and purchase decisions. Based on the results of the analysis, it is known that there is a significant influence with a positive direction between service quality and purchase decisions. Purchase decisions are statistically proven to have a positive and significant influence on customer loyalty. Purchase decisions are proven to fully mediate the relationship between customer retention and customer loyalty. Purchase decisions are proven to mediate the full relationship between service quality and customer loyalty. Keywords: Service Quality, Purchase Decision, Loyalty, Customer Retention